Pengaruh Layanan Bimbingan Klasikal Teknik Assertive Training Terhadap Resiliensi Akademik Mahasiswa Bidikmisi Angkatan 2019 - Intan Belqis Khumairoh; Arifin Nur Budiono; Fakhruddin Mutakin (Journal on Education, 2024)
Students are individuals pursuing higher education. The Bidikmisi program is a government-funded educational assistance provided through the Ministry of Education and Culture, distributed via Higher Education Services Institutions. This program offers financial aid to students until they graduate on time, with requirements including timely completion of studies. Universitas Islam Jember is one of the universities implementing this program, with most of its students being recipients of this assistance. Bidikmisi students need to have high spirits and resilience in facing academic challenges. Academic resilience, the ability to overcome difficulties and pressures in education, is crucial for students to complete their studies. This study aims to evaluate the influence of Classical Guidance Services using Assertive Training Techniques on the academic resilience of 2019 Bidikmisi students at Universitas Islam Jember who are completing their final assignments. The research findings show an increase in academic resilience after receiving the guidance services. Statistical analysis indicates a significant difference between pre- and post-treatment, indicating the influence of guidance services on students' academic resilience. This research is the first of its kind and provides a significant contribution to the literature, filling the gap in knowledge about the impact of assertive training techniques on the academic resilience of Bidikmisi students completing their final assignments.